Analysis of macronutrient and micronutrient intake with the incidence of stunting and wasting in toddlers 0-59 months of age at public health center Bojong, Bogor regency - nugrahayu widyawardani; Nurfitri Bustamam; Citra Ayu Aprilia; Niniek Hardini; Panji Octo Prasetio; Kevina Nuraini Yusuf; Muhammad Harahap; Rafi Raihan (Indonesian Nutrition Association, 2024)
Background : Stunting is defined as not achieving optimal height for age. One of the factors of stunting is caused by unbalanced nutrition. This is due to long-term nutrient intake inadequacies that potentially lead to insufficient nutrient requirements from food. Wasting often has symptoms of severe weight loss in the short term. It usually occurs when toddlers do not get a good quality and quantity of food and/or they suffer from recurrent or chronic illnesses. Objective : Assessing the relationship between macro-micronutrient intake with the incidence of stunting and wasting in the Bojong Health Center working area, Bogor Regency July-August 2023 Period. Methods : This research using cross-sectional study was conducted in the working area of Public Health Centre Bojong, Bogor Regency, Indonesia, from July 2023 to August 2023. The number of subjects is 93 subjects. Subjects were recruited using consecutive sampling, toddlers aged 0-59 months and mothers were the respondents who answered questions during interviews, 2x24-hour food recall, SQFFQ. The data in this study was obtained through direct interviews with respondents. Results : Subject macronutrient and micronutrient intake tended to be deficient refer to RDA 2019. There was an association (p=0.000) between the intake of energy, protein, carbohydrates, fat, Fe, Omega 3, Zn, vitamin D, and Ca with the incidence of stunting and wasting. Conclusions : Intakes of energy, protein, carbohydrate, fat, iron, omega-3, zinc, vitamin D, and Ca were significantly lower in children with nutritional problems (stunting and wasting) compared to RDA Indonesian Ministry of Health 2019.